Correlation between Teachers’ Digital Competency and their Self-Efficacy in Managing Online Classes - Sehar, Sara; Alwi, S Khurram Khan (Pakistan Journal of Humanities and Social Sciences, 2023)
Adoption of online teaching platforms for reaching learners and including technologies in lesson delivery was never so crucial before the Pandemic. The shift from regular classroom teaching to distant learning during the pandemic presented many challenges to educators. This study explored the correlation between teachers’ digital competency and their self-efficacy during distant teaching. This research employed a quantitative approach, and a questionnaire was administered to a sample of teaching staff from Karachi's southern region. 155 respondents participated in this research including 85 Nursery teachers and 70 from lower primary level(I–II). The questionnaire included questions on factors for digital competency and teachers’ self-efficacy in separate sections. The digital competency section assessed teachers' proficiency in using digital tools, platforms, and technologies relevant to online teaching. The self-efficacy section measured teachers' beliefs in their capabilities to perform specific tasks related to two factors, which were instructional strategies and students’ engagement. Data analysis included correlation analysis to find the relationship between teachers' digital competency and self-efficacy , instructional strategies and students engagement .Correlation values (.839) , (.727) and (.764) where p < .001 revealed statistically significant relationship between the research variables, concluding the significant role of digital competencies in online teaching. The findings further highlighted the importance of professional training in equipping teachers with technical knowledge and digital competence in order to use online teaching tools with high self-efficacy, which will eventually improve their overall performance in online lesson delivery. Additional qualitative and quantitative research is suggested on further factors that influence teachers’ self-efficacy in their online teaching through digital resources.